Plan estratégico para la cooperativa de taxis CID Campeador en la ciudad de Chone período 2019-2024 - Vergara Esmeraldas, Eduardo Xavier (2020)
The objective of this research was to propose a strategic plan for the Cid Campeador taxi cooperative in the city of Chone, period 2019-2024; in which types of research, methods, techniques and tools were implemented that helped detect shortcomings inside and outside the cooperative. To comply with the investigation, three phases were carried out. The first phase analyzed the current situation of the Cid Campeador taxi transport cooperative, through the application of an interview to partners and clients. In this way, the PEST analysis was developed, to elaborate the EFI and EFE matrices and thus carry out the SWOT matrix, in the same way the combined matrices were established with the purpose of elaborating the competitive profile matrix. In the second phase, the strategic direction for the improvement of the organizational functioning was established, which consisted in the creation of the mission, vision, objectives, policies, values and the design of the strategic objectives. In the third phase, an action plan was developed that contributes to the improvement of administrative management, and the 5W + 1H matrix was carried out, with the purpose of improving the quality of the service.